Low serum vitamin D associated with prediabetes - Ayhan, Recep; Çavuşoğlu Türker, Betül; Ahbab, Süleyman; Türker, Fatih; Ataoğlu, Hayriye Esra (International Journal Of Community Medicine And Public Health, 2018)
Background: This study is performed to evaluate vitamin D levels and metabolic parameters in patients with prediabetes, compared to healthy controls. Methods: This study was conducted between October and December 2013 in İstanbul Haseki Training and Research Hospital, internal medicine department. We enrolled total 247 individuals, 122 prediabetic (PreDM) patients (79 female, 43 male) and 125 control healthy individuals (94 female, 31 male) between 20-65 ages who admitted randomizely to the outpatient clinic with non spesific complaints. FPG, urea, creatinine, calcium, phosphate, albumin, alkaline phosphatase, thyriod stimulan hormon (TSH), 25 hydroxy vitamin D (25[OH]D), parathormon (PTH), c-peptide, insulin were analyzed. Results: Pre DM patients’ mean plasma 25[OH]D level (25.7±14.9 nmol/l) was statistically lower than the control group (31.4±17.8 nmol/l). Pre DM patients’ mean plasma insulin, c-peptide, calcium, PTH, HOMA-IR (10.8±8.7 IU/ml, 3.3±2.0 ng/ml, 9.7±0.4 mg/dl, 56.5±22.5 pg/ml, 3.0±2.68, respectively) levels were statistically higher than the control group’s (6.3±3.8 IU/ml, 2.4±1.0 ng/ml, 9.5±0.5 mg/dl, 44.0±16.0 pg/ml, 1.4±0.8, respectively) mean levels. There were negative correlations between 25[OH]D and BMI (r:- 0.13, p:0.03), FBG (r:- 0.14, p:0.02) and plasma insulin (r:-0.16, p:0.01) values. A multivariate logisitic regression model for prediabetes was performed and variables as female gender, age, HOMA-IR and lower 25[OH]D values were risk factors for pre DM. Conclusions: Serum low 25[OH]D level correlated with insulin resistance and metabolic parameters in prediabetic patients. Also, it may play an important role in the development of type 2 diabetes.